Upaya Pemerintah Kota Tanjungpinang Dalam Percepatan Penurunan Angka Kasus Stunting Berdasarkan Indeks Khusus Penanganan Stunting Provinsi Kepulauan Riau - Muhaimin Wahyudi; Giniung Pardita; Aprilia Sari (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Stunting is a serious chronic nutrition problem in Indonesia, including in the Riau Islands Province. Stunting occurs when a child's growth is stunted and their height is shorter than the standard for their age. This problem can negatively impact a child's physical, cognitive, and social development, and potentially affect productivity and learning abilities in the future. The Riau Islands have unique geographical characteristics with many small islands scattered around the region. This can cause limited access to adequate health and nutrition services, especially on remote islands. In addition, economic factors, low education, and poor sanitation can also be causes of stunting in this area. To improve the quality of life of children in the region, stunting prevention must be a main focus. In the stunting prevention journal, it is important to identify risk factors that contribute to stunting in the Riau Islands, such as unbalanced eating patterns, low access to health and nutrition services, and low public knowledge about the importance of good nutrition.